Efeito de GILZ (Glucocorticoid-Induced Leucine Zipper) na migração de células mononucleares. - Laís Cunha Grossi Ferreira (2022)
Macrophages are critical cells for the resolution of inflammation, contributing to the elimination of pathogens and apoptotic cells, paving the way to the tissue homeostasis. Studies on GILZ (Glucocorticoid Induced Leucine Zipper) in different pre-clinical models of inflammation have shown its anti-inflammatory and pro-resolving actions. Herein, we investigated the role of GILZ in a key event of inflammation resolution named non-phlogistic recruitment of mononuclear cells. To assess GILZ-induced migration, WT mice received an intrapleural injection of PBS, TAT or TAT-GILZ (a cell permeable GILZ-fusion protein) and were euthanized at different time points. Pleural exudates were harvested for morphological leukocyte counts, cell phenotyping, cytokine/chemokine levels measurement and evaluation of protein expression. In a self-resolving model of peritonitis, WT and GILZ-/- mice were inoculated with 1x106 CFU of E. coli and euthanized at different times post-infection. Peritoneal exudates were harvested for morphological leukocyte count, cell phenotyping, determination of apoptosis and efferocytosis, cytokines/chemokines levels measurement and determination of bacterial load. In vitro chemotaxis assays and bacterial phagocytosis were performed. Our data demonstrated that TAT-GILZ induced chemotaxis of RAW264.7 macrophages and that injection of TAT-GILZ into the pleura of WT mice induced a time-dependent influx of leukocytes, which was mainly composed by mononuclear cells with a regulatory phenotype displaying high expression of the M2 markers CD206 and YM1. The migration of these cells was accompanied by increased levels of CCL2, IL-10 and TGF-β. During the resolution phase of peritonitis, which the cellularity is composed mainly by mononuclear cells, GILZ-/- mice showed lower recruitment of these cells associated with lower levels of CCL2. In addition, GILZ-/- mice showed a lower number of M2 macrophages and a lower frequency of the CD206 marker, followed by a higher bacterial load and lower percentage of apoptotic neutrophils and efferocytosis. Bacterial phagocytosis assays using bone marrow-derived macrophages (BMDMs), showed that pre-treatment with TAT-GILZ increased this effector function of macrophages. Conversely, phagocytic capacity from peritoneal cells and BMDMs from GILZ-/- mice was lower than those of cells from WT mice, and this function was rescued by treatment with TAT-GILZ. In summary, GILZ induced CCL2-dependent mononuclear cells recruitment and macrophage polarization for a regulatory phenotype characterized by increased P-STAT3 and up-regulation of IL-10, TGF-β, CD206 and YM1. Conversely, GILZ-/- mice showed numbers of mononuclear cells into the peritoneal cavity and defective macrophage polarization towards a regulatory phenotype, culminating with lower effector function of these cells. Furthermore, in the context of E. coli infection in vitro, TAT-GILZ promoted increased phagocytosis.